Design and Tolerance Analysis of an Axis-Symmetric Mass Comparator Robust to Ground Tilt and Parasitic Forces - 윤경택 (The Graduate School, Ajou University, 2024)
정밀 질량 측정은 다양한 과학 및 산업 분야에서 널리 사용되는 핵심 기술이며, 질량 측정 범위 및 요구되는 측정 성능에 따라서 다양한 측정 원리를 가진 질량 측정 기구들이 존재한다. 그 중 전자기 보상 방식 (Electromagnetic force compensation, EMFC) 원리는 유연기구 메커니즘의 높은 기계적 민감도와 나노미터급 위치 센서의 분해능을 통해 100 μg 급 반복능과 10 μg 분해능을 가지며 측정 정밀도를 가지며 산업계에 널리 사용되는 질량 측정 기기 중 가장 정밀하다. 그러나 EMFC 질량 측정 시스템이 높은 민감도를 가진 만큼 다양한 외적 내적 요인들에 의해 측정 불확도가 발생할 수 있다. 그 중 지면 기울임 상황과 편심 상황은 EMFC 시스템에 기생 힘, 모멘트가 인가되어 측정 오차가 발생하는 대표적인 상황이다. 또한 유연 기구 메커니즘의 가공 및 조립 시 발생하는 설계 공차는 유연기구 메커니즘의 작동을 방해하여 성능을 저하시킬 수 있다. 이를 해결하기 위해 선행 연구는 볼 스크류나 보조 질량의 위치를 조절하여 기생 힘이나 공차로 인해 발생한 측정 오차를 저감 시켰다. 그러나 조정을 위한 시간과 비용이 소모되며 추가적인 기구 부 설계로 인해 시스템의 복잡성이 증가한다._x000D_ 본 논문에서는 축 대칭형 구조와 다중 EMFC 메커니즘을 활용하여 원천적으로 기생 힘에 민감한 질량 비교기를 제안한다. 제안하는 다중 전자기 보상방식 축 대칭형 질량 비교기는 별도의 조정 절차 없이 기생 힘에 대한 영향을 최소화할 수 있으며 이를 통해 측정 절차를 간소화하고 복잡한 조정 장치를 설계하지 않아도 된다. 제안하는 시스템은 삼중 컴파운드 가이드 메커니즘과 트라이-레버 메커니즘으로 구성된다. 삼중 컴파운드 가이드 메커니즘의 경우, 측정 방향 강성은 기존 EMFC와 유사한 수준으로 민감하면서 기생 방향으로는 높은 강성을 확보하여 시스템의 강건성을 극대화한다. 트라이-레버 메커니즘의 3개의 독립된 측정 유닛이 병렬로 축 대칭 구조로 구성되며 기생 모멘트가 작용했을 때 각 유닛이 서로 반대 방향으로 힘을 보상하여 기생 모멘트를 상쇄하는 균형 잡기 기능을 가진다. 이 기능을 통해 시스템에 작용하는 기생 힘, 모멘트로 인해 발생한 측정 불확도를 효과적으로 감소시킬 수 있다._x000D_ 제안한 메커니즘을 분석하기 위해 다물체 질량-스프링 행렬로 시스템을 해석하는 메트릭스 방법을 통해 유연기구 메커니즘 모델링과 파라미터 스터디를 진행하였다. 그리고 이를 통해 시스템의 강성과 동적 모드를 분석하여 동적 안정성을 가지면서 기계적 민감도를 최대화하도록 메커니즘을 설계하였다. 또한 각 측정 유닛을 구성하는 분해능 6 nm를 가진 위치 센서와 높은 열적 안정성을 가지는 전자기 구동기 역시 설계하였다._x000D_ 도출된 설계 값을 바탕으로 프로토타입을 제작하였으며, 실험을 통해 도출한 시스템의 측정 방향 강성은 64.2 N/m로 기존 EMFC와 동일한 수준의 높은 기계적 민감도를 가진다. 또한 1 kg 질량 기준 분해능 0.49 mg, 반복능 0.7 mg로 질량 측정 성능 역시 기존 EMFC와 비슷한 수준을 가졌다. 그리고 지면 기울임과 편심 하중 상황을 시뮬레이션 하여 기생 힘이 작용하였을 때 제안한 시스템이 원천적으로 기생 힘에 영향을 받지 않음을 확인하였으며 실험을 통해 비교 검증하였다. _x000D_ 설계 공차에 대한 분석은 유연기구 메커니즘 모델을 통해 해석하였다. 이 때 질량 비교기의 힘 평형 상태를 구하는 과정에서 최적화 알고리즘을 활용하여 공차가 존재하여 해를 구하기 어려운 블랙박스 모델에서도 쉽게 힘 평형 상태를 찾을 수 있었다. 구축한 모델을 바탕으로 파라미터 분석과 몬테카를로 방법을 통해 제안하는 시스템에 성능을 결정짓는 핵심 공차가 레버와 커플러의 두께인 것을 확인하였다. 해당 결과는 EMFC 시스템 설계 시 공차에 대한 중요한 지침이 될 것으로 판단된다._x000D_ 최종적으로 불확도 평가를 통해 제안한 축 대칭형 다중 EMFC 방식이 기존 EMFC와 동등한 수준의 측정 성능을 가지면서 기생 힘에 대해 높은 강건성을 확보할 수 있음을 확인하였다. 따라서 제안된 축 대칭 다중 EMFC 구조는 기생 힘이나 모멘트에 강한 질량 측정 시스템 및 힘/토크 센서 개발에 적용될 수 있을 것으로 기대된다.|Precision mass measurement is a core technology widely used in various scientific and industrial fields. Mass measurement instruments with various measurement principles exist depending on the mass measurement range and required measurement performance. Among them, the electromagnetic force compensation (EMFC) principle has achieved high repeatability of 100 μg and resolution of 10 μg through the high mechanical sensitivity of the compliant mechanism and the nanometer-level position sensor. However, as the EMFC mass measurement system has high sensitivity, measurement uncertainty may occur due to various external and internal factors. Among them, ground tilt and eccentric loading are representative situations in which parasitic forces or moments are applied to the EMFC system, resulting in measurement uncertainties. Additionally, tolerances that occur during fabrication and assembly of the compliant mechanism may interfere with the operation of the compliant mechanism. To solve this problem, previous research focused on adjustment method through ball screw or trim mass to reduce measurement errors caused by parasitic forces or tolerances. However, time and cost for adjustment are consumed, and the complexity of the system increases._x000D_ In this paper, a mass comparator is proposed that is fundamentally insensitive to parasitic forces by utilizing an axis-symmetric structure and multi-EMFC mechanisms. The proposed multi-EMFC axis-symmetric mass comparator can minimize the influence of parasitic forces without an additional adjustment procedure, which simplifies the measurement procedure and eliminates the need to design a complex adjustment device. The proposed system consists of a triple compound guide mechanism and a tri-lever mechanism. In the case of the triple compound guide mechanism, the stiffness in the measurement direction is sensitive to a level similar to that of the conventional EMFC, while securing high stiffness in the parasitic direction to maximize the robustness of the system. The three independent measuring units of the tri-lever mechanism are composed of an axis-symmetric structure in parallel. When a parasitic moment acts, each unit compensates for the parasitic moment by generating a counterbalancing force in the opposite direction. This mechanism can effectively reduce measurement uncertainty caused by parasitic forces and moments acting on the system._x000D_ To analyze the proposed mechanism, compliant mechanism modeling and parametric study were conducted through the matrix method of analyzing the system with a multibody mass-spring system. Through the model, stiffness and dynamic mode of the system were analyzed and the mechanism was designed to maximize mechanical sensitivity while maintaining dynamic stability. In addition, a zero-position sensor with a resolution of 6 nm and an electromagnetic actuator with high thermal stability that constitute each measurement unit were also designed._x000D_ A prototype was fabricated based on the derived design values, and the stiffness in the measured direction of the system derived through experiments was 64.2 N/m, showing the same high mechanical sensitivity as the conventional EMFC. In addition, the mass measurement performance was also at the almost same level as the conventional EMFC, with a resolution of 0.49 mg and a repeatability of 0.7 mg based on 1 kg mass. Moreover, by simulating ground tilt and eccentric loading situations, it was confirmed that the proposed system was inherently unaffected by parasitic forces. The results were additionally compared and verified through experiments. _x000D_ The tolerance was analyzed through a compliant mechanism model. At this time, in the process of finding the force equilibrium state of the mass comparator, an optimization algorithm was used to easily find the force balance state even in the black box model, which was difficult to find a solution due to tolerances. Based on the constructed model, it was confirmed through parameter analysis and Monte-Carlo simulation that the key tolerance that determines the performance of the proposed system was the thickness of the lever and coupler flexure. The results are expected to serve as important guidelines for tolerances when designing EMFC systems._x000D_ Finally, through uncertainty evaluation, it was confirmed that the proposed axis-symmetric multi-EMFC mass comparator has measurement performance equivalent to that of the conventional EMFC and can secure high robustness against parasitic forces. Therefore, it is expected that the proposed axis-symmetric multi-EMFC structure can be applied to the development of mass measurement systems or force/torque sensors that are resistant to parasitic forces or moments.
학위논문(박사)--기계공학과,2024. 8
Keywords: compliant mechanism; electromagnetic force compensation; mass comparator; mass measurement; tolerance analysis